IMF Survey, Volume 31, Issue 23. (IMF Survey; IMF Survey ;, 2002)
IMF Managing Director Horst Kohler traveled to Latin America on December 6-12 to offer the IMF's support to the region, where several large countries are working hard to stabilize their economies, following Argentina's difficulties. 'At the end of the trip,' Kohler said, 'I remain convinced that lessons from successes in the region can help point the way forward for other countries currently experiencing difficulties.' Kohler's three-nation tour, which he undertook at the invitation of the presidents of Brazil, Colombia, and Chile, was his second visit to Latin America since he took over the reins at the IMF in May 2000.